The unfinished life of Addison Stone - Griffin, Adele (Soho Teen, 2014)
When a celebrated New York City teenager, known for her subversive street art, mysteriously dies, her life is examined in a series of interviews with her parents, friends, boyfriends, mentors, and critics.